FREEZE DRYING AND MOISTURE ADSORPTION KINETICS OF KEFIR POWDER - ISLEROGLU, H. (Italian Journal of Food Science, 2019)
Freeze drying and moisture adsorption behaviour of kefir powder were investigated by fitting the experimental drying data to ten thin layer drying and sorption isotherm models. Moisture adsorption isotherms of kefir powder were determined at 5-35°C and within the range of 0.11–0.88 water activity. By statistical comparison of the values, Midilli et al. was found to be the best model describing the freeze drying behaviour. The GAB and Oswin equations gave the closest fit to the adsorption data over the tested range of temperatures and water activities. Additionally, adsorption isotherms data were used to determine the thermodynamic properties such as isosteric heat, sorption entropy and Gibbs free energy. The enthalpy entropy compensation was valid for the adsorption process and showed that the process was controlled by the enthalpy. Gibbs free energy was negative at all of the tested temperatures, which indicates that moisture adsorption of kefir powder was a spontaneous process.